Dragons eat noodles on Tuesdays - Stahl, Jon; Bentley, Tadgh (New York : Scholastic Press, 2019)
While two monsters argue over how the story they are telling should go, Dennis, a very hungry dragon, is listening nearby--and he has very definite ideas about how this story should end.
jb
Keywords: Dragons -- Juvenile fiction; Monsters -- Juvenile fiction; Storytelling -- Juvenile fiction; Humorous stories; Dragons -- Fiction; Monsters -- Fiction; Storytelling -- Fiction; Humorous fiction; Picture books